The Role of Artificial Intelligence in Marketing Innovation - Silalahi, Verry Albert Jekson Mardame; Simanjuntak, Amoi Sanyo; Siahaan, Rahel Sintadevi; Tangkudung, Audrey Gamaliel Dotulong (Jurnal Multidisiplin Madani, 2024)
Artificial Intelligence (AI) capabilities have become very important in the modern marketing world due to its expertise in analyzing data in depth, predicting consumer behavior, and improving the efficiency of marketing campaigns. The use of artificial intelligence (AI) allows companies to achieve better results in digital marketing by means of content personalization and ad optimization. The purpose of this research is to identify and analyze the role of artificial intelligence in marketing innovation, especially in developing new marketing strategies and improving the effectiveness and efficiency of marketing campaigns. This research uses a qualitative method with a case study approach technique. Data were obtained through semi-structured interviews, focus group discussions (FGDs), and direct observation of five companies that use AI in their marketing strategies. Thematic analysis was used to identify key themes from the collected data. The study shows that artificial intelligence (AI) improves customer personalization and segmentation, operational efficiency, and customer sentiment analysis. AI can also predict sales more precisely and optimize digital advertising, which helps improve overall marketing performance. The application of artificial intelligence (AI) in marketing has a major positive impact on the effectiveness and efficiency of marketing campaigns. These results can provide useful advice for marketers in utilizing artificial intelligence more effectively, as well as contribute to research on the role of artificial intelligence in marketing innovation